2015
DOI: 10.1186/s12885-015-1710-2
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation chemotherapy may improve survival for patients with locally advanced non-small-cell lung cancer receiving concurrent chemoradiotherapy - retrospective analysis of 203 cases

Abstract: BackgroundFor patients with locally advanced non-small-cell lung cancer (LA-NSCLC), the role of consolidation chemotherapy (CCT) following concurrent chemoradiotherapy (CRT) is partially defined. The aim of this study was to evaluate the efficacy and toxicity of CCT.MethodsThe characteristics of LA-NSCLC patients treated with curative concurrent CRT from 2001 to 2010 were retrospectively reviewed.ResultsAmong 203 patients, 113 (55.7 %) patients received CCT. The median number of delivered CCT was 3 and 89.4 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Consolidation chemotherapy (CCT) after initial treatment is intended to improve cancer patient outcomes and has shown efficacy in some cancers, such as cervical 10 and non-small-cell lung cancer 11 . However, reports on CCT for patients with esophageal cancer after dCRT are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Consolidation chemotherapy (CCT) after initial treatment is intended to improve cancer patient outcomes and has shown efficacy in some cancers, such as cervical 10 and non-small-cell lung cancer 11 . However, reports on CCT for patients with esophageal cancer after dCRT are rare.…”
Section: Introductionmentioning
confidence: 99%
“…The role of consolidation CT after CCRT for locally advanced NSCLC still remains unclear. Consolidation CT may improve OS of patients with locally advanced NSCLC receiving CCRT, but not the response rate and PFS . Moreover, analysis failed to show evidence that CCRT provided any significant survival benefit for locally advanced NSCLC .…”
Section: Discussionmentioning
confidence: 93%
“…In a retrospective analysis of 203 LA-NSCLC patients, Liu et al found that CCT might prolong survival compared with CRT alone. The benefit was mostly observed in males, patients < 60 years of age, with non-squamous histology, pre-treatment KPS ≥ 80, Stage IIIB, stable disease, and radiotherapy dose ≥ 60 Gy [9]. In a similar Turkish study, Stage IIIB NSCLC patients treated with CRT followed by CCT had a superior outcome in terms of PFS and OS when compared to induction chemotherapy followed by CRT or exclusive chemoradiotherapy groups [15].…”
Section: Discussionmentioning
confidence: 99%
“…The Southwest Oncology Group had treated patients with concurrent CRT followed by a consolidation docetaxel monotherapy and achieved a promising median survival of 26 months [8]. A retrospective analysis of 203 cases showed that CCT might prolong survival compared with exclusive CRT for LA-NSCLC, especially for males, patients < 60 years of age, with non-squamous histology, pre-treatment KPS ≥ 80, Stage IIIB, stable disease, and radiotherapy dose ≥ 60 Gy [9]. In contrast, a recent pooled analysis of 45 studies on CCT revealed no survival benefit for the LA-NSCLC patients [2].…”
Section: Introductionmentioning
confidence: 99%